Multigenerational Exposure to Heat Stress Induces Phenotypic Resilience, and Genetic and Epigenetic Variations in Arabidopsis thaliana Offspring - Yadav, Narendra Singh; Titov, Viktor; Ayemere, Ivie; Byeon, Boseon; Ilnytskyy, Yaroslav; Kovalchuk, Igor (Frontiers in Plant Science, 2022)
Plants are sedentary organisms that constantly sense changes in their environment and react to various environmental cues. On a short-time scale, plants respond through alterations in their physiology, and on a long-timescale, plants alter their development and pass on the memory of stress to the progeny. The latter is controlled genetically and epigenetically and allows the progeny to be primed for future stress encounters, thus increasing the likelihood of survival. The current study intended to explore the effects of multigenerational heat stress in Arabidopsis thaliana. 25 generations of Arabidopsis thaliana were propagated in the presence of heat stress. The multigenerational stressed lineage F25H exhibited a higher tolerance compared to control progeny F25C. F25H stressed progeny also exhibited the elevated frequency of homologous recombination. A comparison of genomic sequences revealed that F25H lineage had a three-fold higher number of mutations (SNPs and INDELs) as compared to the parallel (F25C) and parental (F2C seeds used as parental control because F1C and F0 generations seeds were no more viable) lineages, suggesting that heat stress induced genetic variations in the heat-stressed progeny. The F25H stressed progeny showed a 7-fold higher number of non-synonymous mutations than the parental non-stress line which might lead to biological variations. Methylome analysis revealed that the F25H stressed progeny showed a lower global methylation level in the CHH context than the control progeny. The F25H and F25C lineages were different from the parental control lineage F2C by 66,491and 80,464 differentially methylated positions (DMPs), respectively, indicating that many epigenetic variations were likely spontaneous in nature. F25H stressed progeny displayed higher frequency of methylation changes in the gene body and lower in the body of Transposable Elements (TEs). Gene Ontology analysis revealed that CG-DMRs were enriched in processes such as response to abiotic and biotic stimulus, cell organizations and biogenesis, and DNA or RNA metabolism. Hierarchical clustering of these epimutations separated the heat stressed and control parental progenies into distinct groups which revealed the non-random nature of epimutations. Overall, our study showed that progenies derived from multigenerational heat stress displayed a notable adaption in context of phenotypic, genotypic and epigenotypic resilience.